Functional Requirements, Design and Implementation of a Social Network Research Data Archive - Dallas, Costis; Kelpšienė, Ingrida; Laužikas, Rimvydas; Gribovskis, Justas (Information & Media, 2024)
In the era of digital communication, social networking platforms have become important tools for the creation and dissemination of collective memory and identity. However, the dynamic nature of these platforms, together with their commercial nature and limited archiving capabilities, pose a number of challenges for researchers seeking to research conversations on heritage, history, memory and identity on social networking sites. This article presents a digital research data archive that helps address these challenges, and also shares best practices in creating and practically applying this archive, enabling the semantic and comprehensive collection, storage, visualization, and analysis of social media discussions.
Keywords: research data archive; social media; digital memory; digital heritage; digital archiving